Peer victimization in youth from immigrant and non-immigrant US families. (December 2014) - Sulkowski, Michael L.; Bauman, Sheri; Wright, Savannah; Nixon, Charisse; Davis, Stan
The phenomenology of peer victimization in youth from immigrant and non-immigrant US families was investigated in the current study. Specifically, differences in how youth were victimized, their responses to being victimized, and how peer bystanders responded to peer aggression incidents involving youth from these respective groups were investigated. Data were collected from two subsets of youth involved in a national research project. Results indicate that youth from immigrant families are more likely than their non-immigrant peers to report being victimized by physical aggression and to be victimized because of issues related to their race, religion, and family income. In addition, youth from immigrant families were more likely to report that their own responses to peer aggression were less likely to lead to positive outcomes and that peer bystander interventions did not benefit them as much as these interventions benefited their non-immigrant peers. Lastly, a concerning number of youth from immigrant families reported that both their own and bystander responses to peer aggression actually resulted in negative outcomes for them.